Perceptions of cultural and provisioning ecosystem services and human wellbeing indicators amongst indigenous communities neighbouring the greater limpopo transfrontier conservation area - N.A. Nyathi; W. Musakwa; D.M. Azilagbetor; N.J. Kuhn (Heliyon)
Nature plays a crucial role in providing ecosystem services (ESs) essential for human wellbeing and biodiversity conservation in rural areas. However, existing paradigms often lack an integrative approach towards rural livelihoods and wellbeing, highlighting the need for a comprehensive understanding of the relationship between human wellbeing (HWB) and ESs. The area around the Greater Limpopo Transfrontier Conservation Area (GLTFCA) offers such ESs to indigenous people who rely heavily on these natural resources. Thus, this study aimed to quantify indigenous people's perceptions of cultural and provisioning ESs and their link to human wellbeing in villages adjacent to the GLTFCA. Key informant interviews were initially conducted to identify ESs as perceived by the participants. Subsequently, face-to-face surveys were carried out in 9 wards across South Africa and Zimbabwe, involving 350 participants. Respondents were asked about the availability of ESs, their levels of degradation, drivers of change, and the impact on their wellbeing. Responses were captured using Likert scales, and multiple regression models analysed the relationships between socio-demographic characteristics and ESs. Results indicated that indigenous people perceived both cultural and provisioning ESs to be available but degrading, with provisioning services degrading more rapidly. Climate change, legislation/policies, and poverty were identified as key drivers of this change. Socio-demographic factors such as gender, nativeness, and employment level influenced perceptions of both ESs. Overall, participants reported that both ESs contribute to their human wellbeing and livelihoods through life satisfaction, happiness, living standards, safety, security, and good health. Finally, this study's findings uniquely offer a baseline for these ESs accounting, demonstrating their direct and indirect benefits to indigenous communities' livelihoods and well-being.